Price Environment for Gold and Silver in the Context of the Development of COVID-19 - Baranova, Valeria; Sergienko, Olena; Stepurina, Svitlana; Lyashenko, Vyacheslav (My University, 2020)
The precious metals market is an integral part of the overall financial market. This part of the financial market plays an important role in the redistribution of financial flows. The precious metals market is currently under the influence of factors related to the spread of the COVID-19 pandemic. We investigated the dynamics of gold and silver prices in the context of the current pandemic development. For this analysis, we use the wavelet ideology. The results can be used in exchange trading in precious metals, investing in gold and silver.
Keywords: sale price; gold; silver; financial market; COVID-19; wavelet coherence